2015
DOI: 10.1093/cid/civ217
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Use and Reduced Risk of Insulin Resistance in HIV-HCV Infected Patients: A Longitudinal Analysis (ANRS CO13 HEPAVIH)

Abstract: Cannabis use is associated with a lower IR risk in HIV-HCV-coinfected patients. The benefits of cannabis-based pharmacotherapies for patients concerned with increased risk of IR and diabetes need to be evaluated in clinical research and practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…This figure is in line with results from a previous study on the same cohort, which showed a protective effect of cannabis use on insulin resistance . Other studies in the general population found similar results regarding cannabis use and insulin resistance .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This figure is in line with results from a previous study on the same cohort, which showed a protective effect of cannabis use on insulin resistance . Other studies in the general population found similar results regarding cannabis use and insulin resistance .…”
Section: Discussionsupporting
confidence: 92%
“…Spontaneous HCV clearers could also be included (second enrolment phase). Further information about the ANRS CO13‐HEPAVIH cohort design is available elsewhere . The cohort received approval from the Comité de Protection des Personnes Ile‐de‐France III (Institutional Review Board).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, others showed no effect of smoked marijuana on hepatitis C virus (HCV) progression in patients with human immunodeficiency virus (HIV) . Moreover, cannabis use was associated with less insulin resistance in HIV‐HCV‐coinfected patients . Thus, more research is required to elucidate the role of ECs in CLD, because ECs might exert positive as well as negative effects, indicating a note of caution in the use of these nonspecifically targeted molecules and their modulators (endocannabinoid‐degrading enzymes inhibitors) or exogenous phytocannabinoids as therapeutics for the treatment of CLD.…”
Section: Ecs In Cldmentioning
confidence: 99%